FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN PENGGUNA ASURANSI MANDIRI INHEALTH TERHADAP PELAYANAN POLI RAWAT JALAN DI RS HERMINA PALEMBANG - Lisneni Dewi; Catur Rio Wahyudi (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2020)
Service quality is a form of consumer (patient) assessment of the level of service received by the expected level of service. If it is not in line with patient expectations, it will be an input for health care organizations to try to fulfill it. Hermina Hospital Palembang increased outpatient visits, one of them is mostly patients of health insurance. One of the most participants who access Hermina Hospital services are those of Mandiri Inhealth Insurance. This study aims to determine the relationship of patient satisfaction using Mandiri Inhealth insurance to outpatient Poly services at Hermina Hospital Palembang in 2019. This research is an analytical survey of